Quantification of magnetic nanoparticles by compensating for multiple environment changes simultaneously. Issue 1 (6th December 2019) - Shi, Yipeng; Jyoti, Dhrubo; Gordon-Wylie, Scott W.; Weaver, John B.
Abstract : A novel two-dimensional scaling method is demonstrated to improve the accuracy of nanoparticle quantification when multiple effects are present. Abstract : The quantification of magnetic nanoparticles is important for many applications, especially for in vivo biosensing. The magnetization harmonics used in spectroscopy of magnetic nanoparticles can be used to estimate nanoparticle number or weight. However, other effects such as temperature or relaxation time change can also influence the nanoparticle magnetization. Therefore, it is necessary to compensate for these factors when estimating the amount of magnetic nanoparticles. This paper shows through simulation that a two-dimensional scaling method can be used to improve the accuracy of nanoparticle quantification, especially when multiple effects are present which can influence the nanoparticle magnetization. Finally, an experiment was performed on a Magnetic Spectroscopy of Brownian motion (MSB) apparatus to demonstrate this method, and nanoparticle weight was determined with a mean error of 1.3 ng (1.81%).